Pemberdayaan Kelompok Tani Wanita Kharisma Sejati melalui Penyiraman Berbasis IoT pada Tanaman Hortikultura - Anwar, Anwar; Nugraha, Syaiful; Malesi, Wa Ode Asriyanti Wida; Sembiring, Jefri; Yusuf, Mani; Rizal, Abdul; Kusumah, Rangga; Pramudya, Febri Nur (Kadiri University, 2025)
The Kharisma Sejati Women's Farmers Group in Sumber Mulya Village, Kurik District, Merauke Regency, faces challenges in manually watering horticultural crops using dippers, buckets, and hoses. This method was time-consuming, labor-intensive, and wasteful, while water sources rely solely on reservoirs and rainwater ponds. To address these issues, a community service program was conducted in the form of training and implementation of an Internet of Things (IoT)-based irrigation system controlled by a smartphone application. This community service program aims to introduce and train the Kharisma Sejati Women's Farmers Group in the use of an IoT-based irrigation system, and to implement it on horticultural land to improve water efficiency and reduce work time. The implementation method included five stages: outreach, technical training, plot demonstrations, mentoring and evaluation, and program sustainability planning. The results showed that the IoT-based irrigation system can save up to 40% of water time and reduce water use by around 30% compared to manual methods. In addition, the application of this technology makes chili plant growth more uniform and improves the digital skills and confidence of women's farmer group members in managing modern agriculture. The program's main advantages are its practicality, water efficiency, consistency, and ability to increase horticultural productivity. Its limitations include its dependence on electricity, network connectivity, and initial adaptation to the application. Going forward, the program has the potential to be developed through more precise technology integration, implementation with other farmer groups, infrastructure support, and the use of digital markets, making it a model for sustainable agricultural innovation in the Merauke region. Kelompok Tani Wanita Kharisma Sejati di Kampung Sumber Mulya, Distrik Kurik, Kabupaten Merauke menghadapi kendala penyiraman tanaman hortikultura yang masih dilakukan secara manual menggunakan gayung, ember, dan selang. Cara ini membutuhkan waktu lama, tenaga besar, serta boros air, sementara sumber air hanya bergantung pada waduk dan kolam tadah hujan. Untuk mengatasi masalah tersebut, dilakukan program pengabdian berupa pelatihan dan penerapan sistem penyiraman berbasis Internet of Things (IoT) yang dikendalikan melalui aplikasi smartphone. Pengabdian ini bertujuan mengenalkan dan melatih Kelompok Tani Wanita Kharisma Sejati dalam penggunaan sistem penyiraman berbasis IoT, serta mengimplementasikannya pada lahan hortikultura guna meningkatkan efisiensi air dan waktu kerja. Metode pelaksanaan meliputi lima tahap: sosialisasi, pelatihan teknis, demonstrasi plot, pendampingan dan evaluasi, serta perencanaan keberlanjutan program. Hasil kegiatan menunjukkan bahwa sistem penyiraman berbasis IoT mampu menghemat waktu penyiraman hingga ±40% dan penggunaan air sekitar ±30% dibandingkan metode manual. Selain itu, penerapan teknologi ini membuat pertumbuhan tanaman cabai lebih seragam serta meningkatkan keterampilan digital dan kepercayaan diri anggota kelompok tani wanita dalam mengelola pertanian modern. Kelebihan utama program ini adalah praktis, hemat air, konsisten, dan mampu meningkatkan produktivitas hortikultura, sedangkan keterbatasannya adalah ketergantungan pada listrik, jaringan, dan adaptasi awal penggunaan aplikasi. Ke depan, program ini berpotensi dikembangkan melalui integrasi teknologi yang lebih presisi, penerapan pada kelompok tani lain. Dukungan infrastruktur, serta pemanfaatan pasar digital, sehingga dapat menjadi model inovasi pertanian berkelanjutan di wilayah Merauke.